Using a mentorship model to localise the Practical Approach to Care Kit (PACK): from South Africa to Nigeria. (23rd October 2018) - Awotiwon, Ajibola; Sword, Charlie; Eastman, Tracy; Ras, Christy Joy; Ana, Prince; Cornick, Ruth Vania; Fairall, Lara; Bateman, Eric; Dube, Audry; Curran, Robyn; Udoekwere, Inemesit; Essien, Unyime-Obong; et al.
Abstract : Nigeria, in its quest to strengthen its primary healthcare system, is faced with a number of challenges including a shortage of clinicians and skills. Methods are being sought to better equip primary healthcare clinicians for the clinical demands that they face. Using a mentorship model between developers in South Africa and Nigerian clinicians, the Practical Approach to Care Kit (PACK) for adult patients, a health systems strengthening programme, has been localised and piloted in 51 primary healthcare facilities in three Nigerian states. Lessons learnt from this experience include the value of this remote model of localisation for rapid localisation, the importance of early, continuous stakeholder engagement, the need expressed by Nigeria's primary healthcare clinicians for clinical guidance that is user friendly and up-to-date, a preference for the tablet version of the PACK Adult guide over hard copies and the added value of WhatsApp groups to complement the programme of face-to-face continuous learning. Introduction of the PACK programme in Nigeria prompted uptake of evidence-informed recommendations within primary healthcare services.